Can a PERMA model-based positive psychological intervention affect the SIA and SWB of vocational college students majoring in nursing in China? - Yang, Jie; Tan, Yingchun; Yao, Chunlin (Frontiers in Psychology, 2024)
The study was conducted to investigate the effects of a PERMA model-based positive psychological intervention on vocational college students' social interaction anxiety and subjective well-being.This is an experimental study in which data were collected through self-administered questionnaire. A total of 261 students from four classes at Caofeidian College of Technology without differences in the levels of social interaction anxiety and subjective well-being were selected as the control group and intervention group randomly. Students in the control group received a traditional psychological intervention, while students in the invention group received a PERMA model-based positive psychological intervention. Thereafter, the research team collected data regarding students' social interaction anxiety and subjective well-being.Based on the result obtained, the mean score for social interaction anxiety in the invention group was significantly lower than those in the control group (42.95 vs. 53.07, p<0.001) and the mean score for subjective well-being was significantly higher than those in the control group (92.58 vs. 87.26, p<0.001).A PERMA model-based positive psychological intervention can effectively relieve the social interaction anxiety of nursing students in vocational colleges, and improve their subjective wellbeing levels.